PENGARUH PENGELUARAN PEMERINTAH, TINGKAT PENGANGGURAN TERBUKA DAN PENDAPATAN ASLI DAERAH TERHADAP TINGKAT KEMISKINAN DI PROVINSI SUMATERA UTARA PADA TAHUN 2017 - 2021 - Reza Juanda; Muhammad Kahpi Siregar (LPPM Universitas Malikussaleh – Indonesia, 2023)
This study examined the influence of government expenditure, open unemployment rate, and local revenue on the poverty rate in North Sumatra Province. This study used the panel data analysis method. Based on the test results, the model selected was a random effect model. Partially, the results showed that government expenditure negatively influenced the poverty rate in North Sumatra, and the open unemployment rate and local revenue did not affect the poverty rate in North Sumatra Province. Simultaneously, government expenditure, the open unemployment rate, and local revenue influenced the poverty rate in North Sumatra Province.